Does slow and steady win the race? Investigating feedback processes in giant molecular clouds. Issue 3 (25th July 2018) - Garratt-Smithson, Lilian; Wynn, Graham A; Power, Chris; Nixon, Chris J
ABSTRACT: We investigate the effects of gradual heating on the evolution of turbulent molecular clouds of mass 2 × 10 6 M⊙ and virial parameters ranging between 0.7 and 1.2. This gradual heating represents the energy output from processes such as winds from massive stars or feedback from high-mass X-ray binaries (HMXBs), contrasting the impulsive energy injection from supernovae (SNe). For stars with a mass high enough that their lifetime is shorter than the life of the cloud, we include an SN feedback prescription. Including both effects, we investigate the interplay between slow and fast forms of feedback and their effectiveness at triggering/suppressing star formation. We find that SN feedback can carve low-density chimneys in the gas, offering a path of least resistance for the energy to escape. Once this occurs the more stable, but less energetic, gradual feedback is able to keep the chimneys open. By funnelling the hot destructive gas away from the centre of the cloud, chimneys can have a positive effect on both the efficiency and duration of star formation. Moreover, the critical factor is the number of high-mass stars and SNe (and any subsequent HMXBs) active within the freefall time of each cloud. This can vary from cloud to cloud due to the stochasticity of SN delay times and in HMXB formation. However, the defining factor in our simulations is the efficiency of the cooling, which can alter the Jeans mass required for sink particle formation, along with the number of massive stars in the cloud.